(untitled) (World Bulletin of Management and Law, 2026)
All the words used in artistic speech create imagery to one degree or another. Because any word expresses its own meaning in the text, and creates an image of an event. There are also special tools that create imagery in the language, which enhances artistic effectiveness based on the figurative expression of thought. One such tool is qualification. Characterization is a kind of trope, which is considered a visual device that provides artistic imagery. Quality is a universal tool. Therefore, this tool is used in all types of speech. It is a visual tool that performs the function of defining a feature of the phenomenon as a sign